DEVELOPING A CEFR-BASED ANALYSIS GRID FOR LISTENING TASKS AND ITEMS - Adriana TODEA (Studia Universitatis Babeş-Bolyai. Philologia, 2019)
Developing a Cefr-Based Analysis Grid for Listening Tasks and Items. Assessing listening abilities in a foreign language on CEFR (Common European Framework of Reference for Languages) standards requires that clear correlations be drawn between CEFR listening comprehension descriptors and the features of the input text and items of specific listening tasks. A CEFR-based analysis grid designed to assess listening tasks and items provides a useful tool of consistent measurement of the conformity of a specific task and its items to the level of proficiency they claim to assess. The present paper analyzes components of the listening comprehension construct in language test situations and builds discriminating scales based on graduating features isolated from CEFR relevant descriptors.